How physical therapists instruct patients with stroke: an observational study on attentional focus during gait rehabilitation after stroke. Issue 10 (8th May 2018) - Kal, Elmar; van den Brink, Henrieke; Houdijk, Han; van der Kamp, John; Goossens, Paulien Helena; van Bennekom, Coen; Scherder, Erik
Abstract: Purpose: People without neurological impairments show superior motor learning when they focus on movement effects (external focus) rather than on movement execution itself (internal focus). Despite its potential for neurorehabilitation, it remains unclear to what extent external focus strategies are currently incorporated in rehabilitation post-stroke. Therefore, we observed how physical therapists use attentional focus when treating gait of rehabilitating patients with stroke. Methods: Twenty physical therapist-patient couples from six rehabilitation centers participated. Per couple, one regular gait-training session was video-recorded. Therapists' statements were classified using a standardized scoring method to determine the relative proportion of internally and externally focused instructions/feedback. Also, we explored associations between therapists' use of external/internal focus strategies and patients' focus preference, length of stay, mobility, and cognition. Results: Therapists' instructions were generally more external while feedback was more internal. Therapists used relatively more externally focused statements for patients with a longer length of stay ( B  = −0.239, p  = 0.013) and for patients who had a stronger internal focus preference ( B  = −0.930, p  = 0.035). Conclusions: Physical therapists used more external focus instructions, but more internally focused feedback. Also, they seem to adapt their attentional focus use to patients' focus preference and rehabilitation phase. Future research may determine how these factors influence the effectiveness of different attentional foci for motor learning post-stroke. IMPLICATIONS FOR REHABILITATION: Physical therapists use a balanced mix of internal focus and external focus instructions and feedback when treating gait of stroke patients. Therapists predominantly used an external focus for patients in later rehabilitation phases, and for patients with stronger internal focus preferences, possibly in an attempt to stimulate more automatic control of movement in these patients. Future research should further explore how a patients' focus preference and rehabilitation phase influence the effectiveness of different focus strategies. Awaiting further research, we recommend that therapists use both attentional focus strategies, and explore per patient which focus works best on a trial-and-error basis.